Cross-shaped hollow MFI molecular sieve, preparation method thereof and application of cross-shaped hollow MFI molecular sieve in catalyst

Cross-shaped hollow MFI molecular sieve was prepared by low seed addition amount and low mode silicon ratio, and catalysts were prepared by alkali treatment and spray drying technology, which solved the problem of insufficient wear resistance of existing MFI molecular sieve catalysts, and achieved high wear resistance and stable catalytic activity.

CN119528167AActive Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311093021.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-29
Publication Date
2025-02-28
Estimated Expiration
2043-08-29

AI Technical Summary

Technical Problem

The existing MFI molecular sieve catalysts have the problem of insufficient wear resistance when circulating at high temperatures, especially in fluidized catalytic cracking/cracking reactions, and the catalyst activity is easily reduced.

Method used

Cross-shaped hollow MFI molecular sieve was prepared by combining low seed addition amount and low mode silicon ratio. Hollow MFI molecular sieve with cross-shaped morphology was obtained by alkali treatment, and mixed with the support material, and spray-dried to prepare the catalyst.

Benefits of technology

The wear resistance of the catalyst is improved, and the thermal wear (5h loss %) is less than 4.2%, maintaining the mechanical strength and catalytic activity of the catalyst, and is especially suitable for the fluidization process of repeated cycle reaction regeneration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004418206980000111
    Figure BDA0004418206980000111
  • Figure BDA0004418206980000112
    Figure BDA0004418206980000112
  • Figure HDA0004418206990000011
    Figure HDA0004418206990000011
Patent Text Reader

Abstract

The invention relates to a cross-shaped hollow MFI molecular sieve, a preparation method thereof and application of the cross-shaped hollow MFI molecular sieve in a catalyst. Crystal grains of the cross-shaped hollow MFI molecular sieve are in a cross-shaped hollow morphology, a mother solution is prepared by combining a seed crystal and a template agent according to a certain charging step and proportion, a parent molecular sieve is synthesized through dynamic crystallization, and then the hollow molecular sieve is obtained through alkali treatment. The cross-shaped hollow MFI can replace an existing MFI molecular sieve to prepare a catalyst, and has the characteristics of good wear resistance and capability of keeping catalytic activity in a fluidization process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts and relates to a cross-shaped hollow MFI molecular sieve catalyst and a preparation method thereof. Background Art

[0002] ZSM-5 molecular sieve is a new structure zeolite molecular sieve with high silicon three-dimensional cross straight channels first developed by Mobile Company in the United States in 1972. This zeolite molecular sieve is oleophilic and hydrophobic, with high thermal and hydrothermal stability. Most of the pore sizes are about 0.55nm, which belongs to medium-pore zeolites. Due to its unique pore structure, it not only provides spatial restriction for shape-selective catalysis, but also provides abundant access channels for reactants and products, and also provides a crystal structure basis for the preparation of industrial catalysts with high selectivity, high activity, and strong resistance to carbon deposition and deactivation. As a result, it has become one of the most important catalytic materials in shape-selective reactions in the petroleum industry. However, its micropore size is small, and there are certain diffusion restrictions in reactions involving macromolecules. Compared with multi-level pore molecular sieves and nanocrystals, hollow materials have the following significant advantages: regular and controllable wall thickness; adjustable overall particle size; large internal hollow cavity, which can be used as a nanoreactor. One method for synthesizing hollow molecular sieves is to treat the synthesized molecular sieves with alkali, but not all existing molecular sieves can be treated to obtain molecular sieves with hollow structures.

[0003] Prior art MFI molecular sieves are used to prepare catalysts, which generally include the steps of mixing, molding and drying the MFI molecular sieve with a carrier component. For example, for fluidized catalytic cracking catalysts, the steps generally include mixing and slurrying the MFI structured molecular sieve with clay, a binder and a matrix material, and spray drying. The average particle diameter of the obtained catalyst is generally 60-80 microns so that the catalyst has good fluidization performance. Since the catalyst circulates in the reactor and the regenerator at high temperature, it is required to have good wear resistance. The prior art generally improves the wear resistance of the catalyst by changing the binder, such as using a binder with good performance or using more binder. The prior art does not involve how to improve the wear resistance of the catalyst by improving and changing the molecular sieve. Summary of the invention

[0004] The first, second and third in the first silicon source, the second silicon source, the third silicon source, the first template and the second template of the present invention are used to distinguish the substances added in different steps and should not be understood as limiting the properties or functions of the silicon source or template.

[0005] The cross shape mentioned in the present invention means that the projection of the MFI molecular sieve crystal particles in at least one direction is in the shape of a "cross".

[0006] The hollow refers to that the MFI molecular sieve crystal has a space surrounded by side walls, and the space may be enclosed inside the crystal, or may have openings in one or more directions communicating with the outside of the crystal.

[0007] The room temperature is: 20-35°C.

[0008] The grain size refers to the size of the widest part of the grain, which can be obtained by measuring the size of the widest part of the grain projection surface in the SEM or TEM image of the sample. The average grain size is obtained by selecting any 10 molecular sieve grains in the SEM or TEM image and calculating their average value. The wall thickness of the grain, or shell thickness, is the thickness of the side wall of the hollow structure of the grain. The wall thickness of any part of a single grain can be measured through the TEM image, and then the average value of 10 grains is taken as the wall thickness of the sample.

[0009] The measurement method of thermal wear refers to standard Q / SH 3360252-2015: The catalyst is purged with 200m / s fluidizing gas at 700°C. The collision and wear between the catalyst particles and the collision and wear between the catalyst and the wall produce fine powder, which is purged into the fine powder collector by the evaluation gas. Collect the fine powder after 1h and 5h of wear respectively, and calculate the thermal wear index based on the mass of the fine powder. Thermal wear (5h loss%) = (mass of fine powder in 5h - mass of fine powder in 1h) / (mass of sample - mass of fine powder in 1h) × 100%

[0010] In the present invention, the relative crystallinity of the molecular sieve is based on the XRD standard ZSM-5 molecular sieve standard sample of the Petrochemical Science Research Institute, and the crystallinity of the standard sample is regarded as 100%.

[0011] The technical problem to be solved by the present invention is to provide a cross-shaped hollow structure molecular sieve and a preparation method thereof.

[0012] Another technical problem to be solved by the present invention is to provide an application of the molecular sieve containing the cross-shaped hollow structure.

[0013] The first aspect of the present invention provides a cross-shaped hollow MFI molecular sieve, wherein the crystal particles of the MFI molecular sieve are in a cross-shaped hollow morphology.

[0014] The second aspect of the present invention provides a method for preparing the cross-shaped hollow MFI molecular sieve, the method comprising:

[0015] A. Preparation of seed molecular sieve, comprising the following preparation steps:

[0016] (A1) dissolving a silicon source (referred to as the first silicon source) and a template (referred to as the first template) in water, and stirring at 30 to 60° C. for 2 to 6 hours; the molar ratio of R / SiO2 is 0.10 to 0.30, and the molar ratio of H2O / SiO2 is 15 to 50, wherein R represents the template;

[0017] (A2) subjecting the product of step (A1) to hydrothermal dynamic crystallization at 140-180° C. for 8-24 hours; the resulting reaction product is recorded as seed solution.

[0018] B. Preparation of cross-shaped hollow MFI molecular sieves, including the following preparation steps:

[0019] (B1) dissolving an alkali source in water and stirring the water to obtain an alkali source solution;

[0020] (B2) mixing an aluminum source with water and stirring to obtain an aluminum source solution; optionally adding a certain amount of a second template solution and an optional organosilicon source;

[0021] (B3) mixing a silicon source (referred to as a second silicon source) with the alkaline source solution obtained in step (B1), stirring at room temperature, for example, for more than 10 minutes, for example, 10 to 30 minutes, and optionally adding a certain amount of a second template solution and an optional organosilicon source;

[0022] (B4) Mix the product obtained in step (B3) with optional water, then add the product obtained in step (B2) under stirring, and stir at room temperature for more than 10 minutes, for example 30 to 60 minutes; obtain a mixed solution, referred to as the first mixed solution; the molar ratio of the first mixed solution is: n(SiO2) / n(Al2O3)=50~200, for example 50~70, n(MB2O) / n(SiO2)=0.25~0.40, n(H2O) / n(SiO2)=60~100, for example 80~95; wherein the SiO2 in the said ratio refers to the SiO2 of the second silicon source, wherein MB refers to an alkali metal, which is one or more of K, Rb, and Cs.

[0023] (B5) adding the seed solution obtained in step (A2) to the first mixed solution in step (B4), stirring at room temperature for 1 to 6 hours, and optionally adding a certain amount of a second template solution and an optional organic silicon source to obtain a second mixed solution; wherein the SiO2 content in the seed solution accounts for 4 to 10% by mass of the SiO2 content in the second silicon source;

[0024] In at least one of steps (B2), (B3) or (B5), a template (referred to as the second template) solution and an optional organosilicon source (referred to as the third silicon source) are added. Preferably, after adding the optional second template and the optional third silicon source in each step, stirring is performed at 30 to 60° C., preferably for more than 0.5 hours, such as 0.5 to 4 hours; the molar ratio of the total amount of the second template including the second template added to (B2), (B3) and / or (B5) (if the second template is not added in a certain step, the amount added is calculated as 0) to SiO2 in the second silicon source is 0.02 to 0.08;

[0025] (B6) subjecting the second mixed solution obtained in step (B5) to hydrothermal dynamic crystallization at 140 to 180° C. for 6 to 48 hours;

[0026] (B7) filtering, washing, drying and calcining the product obtained in step (B6) to obtain a parent molecular sieve;

[0027] (B8) mixing the parent molecular sieve obtained in step (B7) with an alkali-containing solution, stirring at 60 to 90° C. for 20 to 60 min, wherein the alkali content in the alkali-containing solution is 0.4 to 2.0 mol / L; obtaining a solid product; the solid product is a cross-shaped MFI molecular sieve having a hollow structure;

[0028] and optionally (B9) subjecting the solid product obtained in step (B8) to ammonium exchange to obtain an H-type cross-shaped hollow MFI molecular sieve.

[0029] The third aspect of the present invention provides an abrasion-resistant MFI molecular sieve catalyst, comprising a carrier material and an MFI molecular sieve, wherein the MFI molecular sieve crystals have a cross-shaped morphology.

[0030] The present invention also provides a method for preparing the wear-resistant MFI molecular sieve catalyst, comprising the steps of mixing and slurrying the cross-shaped MFI molecular sieve, a carrier material and water, and spray drying.

[0031] The cross-shaped hollow MFI molecular sieve provided by the present invention has cross-shaped grains, and can improve the wear resistance of the prepared MFI molecular sieve-containing catalyst compared with the existing MFI molecular sieves. Due to the hollow structure and the cross-shaped morphology, it has the effect of high accessibility of the active center.

[0032] The present invention adopts a method combining low seed addition amount and low template-silicon ratio to prepare a cross-shaped MFI molecular sieve, and obtains a hollow MFI molecular sieve with a cross-shaped morphology after alkali treatment, without using a large amount of template agent and a large amount of seed, which is conducive to reducing material costs.

[0033] The present invention provides a wear-resistant catalyst containing MFI molecular sieves, which has higher wear resistance than conventional MFI molecular sieve catalysts with the same MFI molecular sieve content, and the thermal wear (5h loss %) can be less than 4.2% by mass. It has high mechanical strength and can maintain a high catalytic activity during the catalyst fluidization process. In particular, for fluidized processes that require repeated cyclic reaction regeneration, such as fluidized catalytic cracking / cracking reactions, the catalyst activity can be maintained, making the catalyst performance relatively stable. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 This is a transmission electron microscope image of the molecular sieve prepared in Example 1. DETAILED DESCRIPTION

[0035] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0036] The cross-shaped hollow MFI molecular sieve provided by the present invention has an average grain size of 800-1500nm, such as 900-1200nm, has a shell layer and a hollow structure in the shell layer, and the shell layer thickness is 100-400nm, such as 150-350nm.

[0037] The catalyst prepared by combining the cross-shaped hollow MFI molecular sieve and a specific particle size carrier material provided by the present invention has a thermal wear (5h loss%) of less than 4.2%. The specific particle size carrier material is silica sol and / or alumina sol, and the catalyst optionally further contains a matrix, such as one or more of clay, alumina, and alumina precursor. The average particle size of the alumina sol carrier material is 5 to 50 nm, and the average particle size of the silica sol carrier material is 5 to 20 nm. In the prepared catalyst, the content of the cross-shaped hollow MFI molecular sieve is 20 to 60% by mass on a dry basis, the content of the alumina sol is 10 to 20% by mass in terms of Al2O3, the content of the silica sol is 5 to 10% by mass in terms of SiO2, and the content of the matrix is ​​10-50% by mass, such as 20-50% by mass.

[0038] The cross-shaped hollow MFI molecular sieve can be an alkali metal type cross-shaped hollow MFI molecular sieve or an H type (ie, hydrogen type) cross-shaped hollow MFI molecular sieve.

[0039] According to the preparation method of the cross-shaped hollow MFI molecular sieve of the present invention, the silicon source described in step (A1) is one or more of methyl orthosilicate or ethyl orthosilicate, and the template agent described in step (A1) is one or more of tetrapropylammonium hydroxide or tetrapropylammonium bromide.

[0040] According to the method for preparing the cross-shaped hollow MFI molecular sieve of the present invention, the grain size of the seed crystal in step (A2) can be 200-800 nm.

[0041] According to the method for preparing the cross-shaped hollow MFI molecular sieve of the present invention, the concentration of the alkali source solution in step (B1) is preferably 10-30% by mass, for example 15-25% by mass. The alkali source is one or more of potassium hydroxide, rubidium hydroxide or cesium hydroxide.

[0042] According to the method for preparing the cross-shaped hollow MFI molecular sieve of the present invention, the concentration of the aluminum source solution in step (B2) is preferably 5-20 mass %, for example 5-15 mass %. The aluminum source can be one or more of aluminum sulfate, aluminum nitrate or aluminum chloride.

[0043] According to the preparation method of the cross-shaped hollow MFI molecular sieve of the present invention, the second silicon source in step (B3) is preferably silica sol. The silica sol can be ammonium silica sol, sodium silica sol or a mixture thereof. The SiO2 content in the silica sol is preferably 15 to 45% by mass, for example, 15% by mass, 25% by mass, 30% by mass, 45% by mass or any two of the values ​​are within the range formed by endpoints.

[0044] According to the preparation method of the cross-shaped hollow MFI molecular sieve of the present invention, an organic silicon source (called the third silicon source) can be added in one or more steps (B2), (B3) and (B5), and the organic silicon source added in step B includes the total amount of the organic silicon source added in steps (B2), (B3) and (B5), and the mass ratio of the total amount of the organic silicon source added in terms of SiO2 to the second silicon source in terms of SiO2 is 5:100 to 10:100.

[0045] According to the method for preparing the cross-shaped hollow MFI molecular sieve of the present invention, when the second template and the optional organosilicon source are added in step (B5), they are preferably first added to the seed solution of step (B5), then stirred at 30 to 60° C. for 0.5 to 4 hours, and then added to the first mixed solution obtained in step (B4).

[0046] According to the preparation method of the cross-shaped hollow MFI molecular sieve of the present invention, the organic silicon source is one or more of methyl orthosilicate or ethyl orthosilicate; the template agent (second template agent) in step B is one or more of tetrapropylammonium hydroxide or tetrapropylammonium bromide.

[0047] According to the preparation method of the cross-shaped hollow MFI molecular sieve of the present invention, in step (B6), the mixed solution obtained in step (B5) (called the second mixed solution) is hydrothermally dynamically crystallized at 140-180° C. for 6-48 hours. For example, the mixed solution obtained in step (B5) can be transferred to a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner, and then hydrothermally dynamically crystallized. The dynamic crystallization is to perform a crystallization reaction on the mixed solution in a moving state, such as under stirring.

[0048] According to the preparation method of the cross-shaped hollow MFI molecular sieve of the present invention, in step (B7), the product obtained in step (B6) is filtered to separate the crystallized molecular sieve from the mother liquor, and then washed to remove the mother liquor attached to the molecular sieve, which can be washed with water, then dried, and then calcined. The calcination temperature is, for example, 450 to 600° C., for example, 500 to 600° C., and the calcination time is, for example, 2 to 12 hours or 2 to 6 hours. The parent molecular sieve is obtained.

[0049] The parent molecular sieve is a cross-shaped MFI molecular sieve. It is a solid molecular sieve. To this end, the present invention further provides an MFI structure molecular sieve, the crystal grains of which are cross-shaped, and the average grain size is 800-1500nm. After the cross-shaped MFI molecular sieve is treated with one step of alkali, the crystal retention is 95%-110%. The alkali treatment is to mix the MFI structure molecular sieve with an alkali-containing solution, stir for 20-60min at 60-90°C, and the alkali content in the alkali-containing solution is 0.4-2.0mol / L. The parent molecular sieve can obtain a hollow cross-shaped MFI molecular sieve after the alkali treatment.

[0050] According to the preparation method of the cross-shaped hollow MFI molecular sieve of the present invention, in step (B8), the parent molecular sieve is mixed with an alkali solution, and stirred at 60 to 90° C. for 20 to 60 minutes to form a hollow structure. Then, after filtering, washing, for example, washing with water to wash away the alkali solution in the treated parent molecular sieve, and drying, a solid is obtained. The alkali solution is, for example, an alkali solution containing one or more of sodium hydroxide, potassium hydroxide, rubidium hydroxide, and cesium hydroxide. The content of alkali in the alkali solution is 0.4-2.0 mol / L, for example, 0.4-1 mol / L.

[0051] According to the preparation method of the cross-shaped hollow MFI molecular sieve of the present invention, preferably, it also includes step (B9): the solid product obtained in step (B8) is treated to obtain an H-type hollow cross-shaped ZSM-5 molecular sieve. One embodiment includes exchanging the solid product obtained in step (B8), such as ammonium exchange, and then drying and roasting. The methods of ammonium exchange, drying and roasting are well known to those skilled in the art. For example, the roasting temperature can be 500-600°C, and the roasting time can be 1-5 hours.

[0052] According to the method for preparing the cross-shaped hollow MFI molecular sieve of the present invention, in a specific embodiment, the preparation steps of the cross-shaped hollow MFI molecular sieve are as follows:

[0053] A. Preparation of seed molecular sieve, including the following preparation steps:

[0054] (1) Dissolve the silicon source and template in water, and heat with stirring at 30-60°C for 2-6 hours;

[0055] (2) transferring the solution of step A(1) into a high pressure hydrothermal reactor and subjecting it to hydrothermal dynamic crystallization at 140-180° C. for 8-24 h;

[0056] (3) The reaction product obtained in step A(2) is recorded as seed solution.

[0057] B. Preparation of cross-shaped hollow MFI molecular sieves, including the following preparation steps:

[0058] (1) dissolving an alkali source in water, stirring evenly, and obtaining an alkali source solution after the alkali source is fully dissolved;

[0059] (2) dissolving an aluminum source in water and stirring evenly to obtain an aluminum source solution, adding a certain amount of a template solution or a mixture of a template and an organic silicon source, and mixing thoroughly to obtain an aluminum source-containing dispersion; the thorough mixing is, for example, stirring at room temperature to 50° C. for more than 1 hour, for example, 1 to 4 hours; wherein the molar ratio of the template to the SiO2 in the silicon source (second silicon source) in step (3) is 0.02 to 0.08

[0060] (3) mixing the silicon source (second silicon source) with the alkaline source solution of step B (1), and stirring at room temperature for 10 to 30 minutes;

[0061] Alternatively, step (2) is replaced by the following (2'), and step (3) is replaced by the following (3'),

[0062] (2') dissolving the aluminum source in water and stirring evenly to obtain an aluminum source solution,

[0063] (3') mixing the silicon source (second silicon source) with the alkaline source solution of step B (1), stirring at room temperature for 10 to 30 minutes; adding a certain amount of template solution or a mixture of template and organic silicon source, stirring, for example, at room temperature to 50° C. for more than 1 hour, for example, 1 to 4 hours; wherein the molar ratio of the template to SiO2 in the silicon source (second silicon source) is 0.02 to 0.08;

[0064] (4) adding the mixed solution obtained in step B(3) or B(3') to a certain amount of water, then adding the product of step B(2) or B(2') under stirring, and stirring at room temperature for 30 to 60 minutes;

[0065] (5) adding a certain amount of the seed solution described in step A (3) to the product of step B (4) and stirring at room temperature for 1 to 6 hours;

[0066] (6) transferring the product obtained in step B (5) to a high-pressure hydrothermal reactor and subjecting it to hydrothermal dynamic crystallization at 140 to 180° C. for 6 to 48 hours;

[0067] (7) filtering, washing, drying and calcining the product obtained in step B (6) to obtain a parent molecular sieve;

[0068] (8) mixing the parent molecular sieve obtained in step B (7) with an alkali-containing solution, stirring at 60 to 90° C. for 20 to 60 min, wherein the alkali content in the alkali-containing solution is 0.4 to 2.0 mol / L;

[0069] (9) The solid product obtained in step B (8) is subjected to ammonium exchange to obtain an H-type cross-shaped hollow MFI molecular sieve.

[0070] According to the wear-resistant MFI molecular sieve catalyst of the present invention, the MFI molecular sieve is preferably the cross-shaped hollow MFI molecular sieve provided by the present invention. In addition to having high wear resistance, the catalyst can also have the effects of high accessibility of active centers and good catalytic performance due to the hollow structure of the cross-shaped hollow MFI molecular sieve.

[0071] The wear-resistant MFI molecular sieve catalyst is preferably a fluidizable catalyst, such as a catalyst for fluidized catalytic cracking. The fluidizable wear-resistant MFI molecular sieve catalyst preferably has an average particle size of 60 to 80 microns. The average particle size is measured according to laser particle size analysis, which is well known to those skilled in the art.

[0072] According to the wear-resistant MFI molecular sieve catalyst provided by the present invention, the thermal wear (5h loss %) of the catalyst is less than 4.2% by mass.

[0073] According to the wear-resistant MFI molecular sieve catalyst provided by the present invention, the carrier material includes aluminum sol, and the average particle size of the aluminum sol is preferably 5 to 50 nm. In one embodiment, the content of the aluminum sol in the catalyst is 10 to 20% by mass in terms of Al2O3.

[0074] According to the wear-resistant MFI molecular sieve catalyst provided by the present invention, the carrier material includes silica sol, and the average particle size of the silica sol is preferably 5 to 20 nm. In one embodiment, the content of silica sol in the wear-resistant MFI molecular sieve catalyst is 5 to 10% by mass in terms of SiO2.

[0075] The average particle size of the aluminum sol and the average particle size of the silica sol were measured by a dynamic light scattering method.

[0076] According to the wear-resistant MFI molecular sieve catalyst provided by the present invention, the carrier material of the wear-resistant MFI molecular sieve catalyst also includes a matrix, and the matrix is, for example, one or more of clay, alumina such as γ-alumina, and pseudo-boehmite.

[0077] In one embodiment, the content of clay in the wear-resistant MFI molecular sieve catalyst can be 0-50 mass %, for example, 10-40 mass %, calculated as dry basis, and the content of alumina and / or pseudo-boehmite can be 0-50 mass %, for example, 10-40 mass %, calculated as Al2O3. The content of each component in the catalyst is calculated according to the raw materials added during preparation.

[0078] The room temperature described in the following examples and comparative examples is 26°C.

[0079] The average particle size of the aluminum sol and the average particle size of the silica sol were measured by dynamic light scattering using a Malvern Zetasizer Nano ZS90 instrument.

[0080] The measurement method of thermal wear is in accordance with standard Q / SH 3360252-2015.

[0081] Example 1

[0082] A. Preparation of seed solution:

[0083] (A1) 39.8 g of ethyl orthosilicate, 42.5 g of tetrapropylammonium hydroxide and 120.0 g of deionized water were mixed and heated at 40° C. with stirring for 4 h;

[0084] (A2) transferring the solution of step (A1) into a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner and subjecting it to dynamic crystallization at 170° C. for 12 h;

[0085] (A3) is taken out after the crystallization is completed and recorded as seed solution 1;

[0086] B Preparation of cross-shaped hollow ZSM-5 molecular sieve:

[0087] (B1) adding 7.86 g of potassium hydroxide to 23.58 g of deionized water and stirring well to obtain an alkaline source solution;

[0088] (B2) adding 1.80 g of aluminum sulfate 18hydrate to 16.2 g of deionized water and stirring well to obtain an aluminum source solution;

[0089] (B3) 36.80 g of silica sol (sodium silica sol, silicon oxide content 30% by mass, pH 9.2, Na2O content 0.22% by mass) was slowly added to the alkali source solution of step (B1), stirred at room temperature for 30 minutes, and then a mixed solution of 8.96 g of tetrapropylammonium hydroxide and 3.50 g of ethyl orthosilicate was added, and stirred at 35° C. for 2 hours;

[0090] (B4) adding 210.82 g of deionized water to the product of step (B3), then adding the aluminum source solution of step (B2) under stirring, and stirring at room temperature for 30 minutes;

[0091] (B5) adding 5.52 g of the seed solution 1 of step (A3) to the product of step (B4), and stirring at room temperature for 4 hours;

[0092] (B6) transferring the mixed solution of step (B5) into a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner, and subjecting it to hydrothermal dynamic crystallization at 170° C. for 48 h;

[0093] (B7) filtering, washing, drying and calcining the product obtained in step (B6) to obtain molecular sieve S-1;

[0094] (B8) molecular sieve S-1 and a sodium hydroxide solution with a concentration of 0.6 mol / L were mixed uniformly, the mass ratio of molecular sieve S-1 to alkaline solution was 1:10, the temperature was raised to 80°C at a heating rate of 4°C / min, and then stirred at this temperature for 30 min, filtered, washed, and dried to obtain molecular sieve S-1-J;

[0095] (B9) molecular sieve S-1-J: ammonium chloride: deionized water were mixed in a mass ratio of 1:1:10, stirred and heated in a water bath at 80°C for 30 min, filtered, washed, and dried, and then the dried solid: ammonium chloride: deionized water were mixed in a mass ratio of 1:0.5:10, and the second ammonium exchange was performed, filtered, washed, dried, and calcined at 550°C for 2 h to obtain a hydrogen-type cross-shaped hollow ZSM-5 molecular sieve, denoted as S-1-JH. Figure 1 This is a transmission electron microscope image.

[0096] Example 2

[0097] A. Preparation of seed solution:

[0098] (A1) 45.6 g of ethyl orthosilicate, 28.9 g of tetrapropylammonium hydroxide and 105.9 g of deionized water were mixed and heated at 40° C. with stirring for 4 h;

[0099] (A2) transferring the solution of step (A1) into a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner and subjecting it to dynamic crystallization at 170° C. for 12 h;

[0100] (A3) is taken out after the crystallization is completed and recorded as seed solution 2;

[0101] B Preparation of cross-shaped hollow ZSM-5 molecular sieve:

[0102] (B1) Add 6.34 g of potassium hydroxide to 28.88 g of deionized water and stir well;

[0103] (B2) adding 1.67 g of aluminum isopropoxide to 19.205 g of deionized water, stirring evenly, then adding a mixed solution of 4.85 g of tetrapropylammonium hydroxide and 2.25 g of ethyl orthosilicate, stirring at 40° C. for 1 hour;

[0104] (B3) adding 40.20 g of silica sol (silicon oxide content 30%) to the alkali source solution of step (B1) and stirring at room temperature for 30 minutes;

[0105] (B4) adding 252.61 g of deionized water to the product of step (B3), then adding the aluminum source solution of step (B2) under stirring, and stirring at room temperature for 30 minutes;

[0106] (B5) adding 9.65 g of the seed solution 2 obtained in step (A3) to the product obtained in step (B4), and stirring at room temperature for 4 hours;

[0107] (B6) transferring the product of step (B5) to a high-pressure hydrothermal reactor with a polytetrafluoroethylene liner and subjecting it to hydrothermal dynamic crystallization at 170° C. for 48 h;

[0108] (B7) filtering, washing, drying and calcining the product obtained in step (B6) to obtain molecular sieve S-2;

[0109] (B8) molecular sieve S-2 and a sodium hydroxide solution with a concentration of 0.8 mol / L were mixed uniformly, the mass ratio of molecular sieve S-2 to sodium hydroxide solution was 1:10, the temperature was raised to 80°C at a heating rate of 4°C / min, and then stirred at this temperature for 30 min, filtered, washed, and dried to obtain molecular sieve S-2-J;

[0110] (B9) The molecular sieve S-2-J: ammonium chloride: deionized water were mixed in a mass ratio of 1:1:10, stirred and heated in a water bath at 80°C for 30 min, filtered, washed and dried, and then the dried solid: ammonium chloride: deionized water were mixed in a mass ratio of 1:0.5:10, subjected to a second ammonium exchange, filtered, washed, dried, and calcined at 550°C for 2 h to obtain a hydrogen-type (H-type) cross-shaped hollow ZSM-5 molecular sieve, denoted as S-2-JH.

[0111] Comparative Example 1

[0112] Comparative Example A conventional hexagonal ZSM-5 molecular sieve with a crystal size of 2.5 μm was selected, and alkali treatment and ammonium exchange were performed according to step (B8) and step (B9) of Example 1, and it was recorded as DS-1-JH. It does not have a hollow structure.

[0113] Preparation of catalytic cracking catalysts in Examples 3-4 and Comparative Example 2

[0114] Among them, the raw materials other than the molecular sieves used are all commercially available products. The average particle sizes of the aluminum sol and silica sol used in each embodiment and comparative example are shown in Table 2.

[0115] (1) mixing molecular sieve, aluminum sol, silica sol, kaolin and pseudo-boehmite slurry and deionized water to form a slurry with a solid content of 40% by mass, and spray drying to obtain catalyst microspheres;

[0116] (4) The catalyst microspheres were calcined at 550 °C for 4 h;

[0117] (5) The calcined catalyst microspheres were exchanged at 80° C. for 1 h according to a mass ratio of catalyst microspheres: ammonium salt: H2O=1:1:10, filtered, and the above exchange and filtration process was repeated once, and then dried, wherein the ammonium salt was ammonium chloride, and the sodium oxide content in the obtained catalytic cracking catalyst was less than 0.15% by mass. The composition of the prepared catalyst is shown in Table 2.

[0118] Table 1

[0119]

[0120] The molecular sieve synthesis ratio is the ratio of the product of step B4. The crystal retention after alkali treatment is the ratio of the crystallinity of the parent molecular sieve obtained in step B7 after alkali treatment to the crystallinity of the parent molecular sieve, for example, the ratio of the crystallinity of S-1-J to the crystallinity of S-1 in Example 1, and the ratio of the crystallinity of S-2-J to the crystallinity of S-2 in Example 2.

[0121] Table 2 Catalyst composition and thermal wear performance

[0122]

Claims

1. An MFI molecular sieve, characterized in that: The crystal grains of the MFI molecular sieve are cross-shaped. After one-step alkali treatment, the crystal retention of the MFI molecular sieve is 95% to 110%, and the average crystal grain size is 800 to 1500 nm.

2. A cross-shaped hollow MFI molecular sieve, characterized in that: The crystallites of the MFI molecular sieve are cross-shaped and hollow in shape.

3. The cross-shaped hollow MFI molecular sieve according to claim 1 or 2, characterized in that: The average crystal size of the cross-shaped hollow MFI molecular sieve is 800-1500 nm, and the shell thickness is 100-400 nm; the cross-shaped hollow MFI molecular sieve can be an H-type cross-shaped hollow MFI molecular sieve.

4. The cross-shaped hollow MFI molecular sieve according to claim 2 or 3, characterized in that: The thermal wear (5h loss %) of the catalyst prepared by combining the molecular sieve with a specific particle size carrier material is less than 4.2% by mass, wherein the specific particle size carrier material is silica sol and / or alumina sol, the average particle size of the alumina sol carrier material is 5 to 50 nm, the average particle size of the silica sol carrier material is 5 to 20 nm, and the catalyst optionally contains one or more matrices selected from clay, alumina, and alumina precursors. The composition of the catalyst includes: 20 to 60% by mass of the cross-shaped hollow MFI molecular sieve calculated on a dry basis, 10 to 20% by mass of the alumina sol calculated on Al2O3, 5 to 10% by mass of the silica sol calculated on SiO2, and 20-50% by mass of the matrix calculated on a dry basis.

5. A method for preparing a cross-shaped hollow MFI molecular sieve, the method comprising: A. Preparation of seed molecular sieve, comprising the following steps: (A1) dissolving a silicon source and a template in water, stirring at 30-60° C. for 2-6 hours; the molar ratio of R / SiO2 is 0.10-0.30, the molar ratio of H2O / SiO2 is 15-50, wherein R represents the template; (A2) subjecting the product of step (A1) to hydrothermal dynamic crystallization at 140-180° C. for 8-24 hours; the resulting reaction product is referred to as seed solution; B. Preparation of cross-shaped hollow MFI molecular sieves, including the following preparation steps: (B1) dissolving an alkali source in water and stirring the water to obtain an alkali source solution; (B2) mixing an aluminum source with water, stirring uniformly to obtain an aluminum source solution, and optionally adding a second template solution and an optional organosilicon source; (B3) mixing the second silicon source with the alkaline source solution obtained in step (B1), stirring at room temperature, for example, for 10 to 30 minutes; optionally adding a second template solution and an optional organosilicon source; (B4) mixing the product obtained in step (B3) with optional water, and then adding the product obtained in step (B2) under stirring, and stirring at room temperature, for example, for 30 to 60 minutes; obtaining a first mixed solution; the molar ratio of the first mixed solution is: n(SiO2) / n(Al2O3)=50 to 200, n(K2O) / n(SiO2)=0.25 to 0.40, n(H2O) / n(SiO2)=60 to 100; wherein the SiO2 in the ratio refers to SiO2 from the second silicon source; (B5) adding the seed solution obtained in step (A2) to the first mixed solution in step (B4), stirring at room temperature for 1 to 6 hours, for example, to obtain a second mixed solution; optionally adding a second template solution and an optional organic silicon source; wherein the SiO2 from the seed solution accounts for 4 to 10% by mass of the SiO2 in the second silicon source; Wherein, in at least one of steps (B2), (B3) or (B5), a second template solution and an optional organosilicon source are added, and the molar ratio of the total amount of the second template added in steps (B2), (B3) and / or (B5) to SiO2 in the second silicon source is 0.02 to 0.08; (B6) subjecting the second mixed solution obtained in step (B5) to hydrothermal dynamic crystallization at 140 to 180° C. for 6 to 48 hours; (B7) filtering, washing, drying and calcining the product obtained in step (B6) to obtain a parent molecular sieve; (B8) mixing the parent molecular sieve obtained in step (B7) with an alkali-containing solution, stirring at 60 to 90° C. for 20 to 60 min, wherein the alkali content in the alkali-containing solution is 0.4 to 2.0 mol / L; obtaining a solid product; and Optionally (B9) the solid product obtained in step (B8) is subjected to ammonium exchange to obtain an H-type cross-shaped hollow MFI molecular sieve.

6. The method according to claim 5, wherein: The silicon source described in step (A1) is one or more of methyl orthosilicate or ethyl orthosilicate, and the template described in step (A1) is one or more of tetrapropylammonium hydroxide or tetrapropylammonium bromide; the organosilicon source described in step B is one or more of methyl orthosilicate or ethyl orthosilicate, and the template described in step B is one or more of tetrapropylammonium hydroxide or tetrapropylammonium bromide.

7. The method according to claim 5, wherein: The grain size of the seed crystals in the seed solution in step (A2) is 200 to 800 nm.

8. The method according to claim 5, wherein: The concentration of the alkali source solution in step (B1) is 10-30% by mass, and the alkali source is one or more of potassium hydroxide, rubidium hydroxide or cesium hydroxide.

9. The method according to claim 5, wherein: The concentration of the aluminum source solution in step (B2) is 5 to 20% by mass, and the aluminum source is one or more of aluminum sulfate, aluminum nitrate or aluminum chloride; In step (B3), the second silicon source is silica sol, and the SiO2 content in the silica sol is 15 to 45% by mass.

10. The method according to claim 5, wherein: The mass ratio of the total amount of the organic silicon source added in the steps (B2), (B3) and (B5) calculated as SiO2 to the mass ratio of the second silicon source calculated as SiO2 is 5:100 to 10:

100.

11. The method according to claim 5, wherein: When the second template and the optional organosilicon source are added in step (B5), they are preferably first added to the seed solution of step (B5), then stirred at 30-60°C for 0.5-4 hours, and then added to the first mixed solution obtained in step (B4).

12. An abrasion-resistant MFI molecular sieve catalyst, comprising a carrier material and an MFI molecular sieve, wherein the MFI molecular sieve is the MFI molecular sieve according to any one of claims 1 to 4 or the cross-shaped hollow MFI molecular sieve obtained by the method according to any one of claims 5 to 11.

13. The wear-resistant MFI molecular sieve catalyst according to claim 12, characterized in that: The thermal wear (5h loss %) of the catalyst was less than 4.2 mass %.

14. The wear-resistant MFI molecular sieve catalyst according to claim 12 or 13, characterized in that: The carrier material includes aluminum sol with an average particle size of 5 to 50 nm, silica sol with an average particle size of 5 to 20 nm and a matrix selected from one or more of clay, alumina and pseudo-boehmite. The content of aluminum sol with an average particle size of 5 to 50 nm in the catalyst is 10 to 20% by mass in terms of Al2O3, the content of silica sol with an average particle size of 5 to 20 nm in the catalyst is 5 to 10% by mass in terms of SiO2, the content of clay is 0 to 50% by mass on a dry basis, and the content of alumina and / or pseudo-boehmite is 0 to 50% by mass in terms of Al2O3.

Citation Information

Patent Citations

  • Universal method for preparation of inorganic hollow microspheres

    CN103949193A

  • Aluminum silicon molecular sieve-aluminum oxide composite material and in-situ growth preparation method thereof

    CN103962171A

  • ZSM-5-based hierarchical porous molecular sieve material and preparation method thereof

    CN104030314A

  • Holocrystalline ZSM-5 molecular sieve catalyst, preparation method and application thereof

    CN104226360A

  • Preparation method of nanometer ZSM-5 zeolite molecular sieve aggregate

    CN109694086A